Machine learning identifies immune-perinatal predictors of infantile hemangioma - Wu, Dongdong; Wan, Neng (Frontiers in Pediatrics, 2025)
BackgroundInfantile hemangioma (IH), the most common vascular tumor of infancy, exhibits hallmark features of immune and inflammatory dysregulation. While most cases are self-limiting, a subset progresses with potentially severe complications. Despite its benign classification, IH offers a unique model to investigate immune-mediated mechanisms in early tumorigenesis. However, risk stratification models incorporating immune-inflammatory markers remain underdeveloped.MethodsA total of 1,466 infants and young children were enrolled, including 81 with IH. Comprehensive perinatal, clinical, and laboratory data were collected. Candidate risk factors were identified using logistic regression. Four machine learning algorithms—XGBoost, Random Forest, Support Vector Machine, and k-Nearest Neighbors—were employed to construct predictive models. Model performance was assessed through internal and external validation. SHapley Additive exPlanations (SHAP) were applied to interpret feature contributions and immune-inflammatory signatures.ResultsKey risk factors included prematurity, multiple gestation, low birth weight, and elevated levels of VEGF, CRP, and SAA—markers linked to inflammation and immune activation. The XGBoost model achieved superior performance, with an AUC of 0.952 (training), 0.935 (internal validation), and 0.870 (external validation). SHAP analysis highlighted SAA, VEGF, and low birth weight as the most influential predictors, reflecting a critical link between innate immune dysregulation and IH development.ConclusionThis study presents a robust, interpretable machine learning model that leverages immune-perinatal features to predict IH risk. Our findings support the notion that IH may serve as a paradigm for inflammation-associated vascular tumorigenesis, with implications for early detection and personalized intervention strategies in immune-driven neoplasms.